2020
DOI: 10.29303/jpm.v15i2.1625
|View full text |Cite
|
Sign up to set email alerts
|

Bioadsorben Salinitas Sederhana berbasis Limbah Lingkungan

Abstract: Penelitian ini bertujuan untuk memberikan informasi serta rekomendasi ilmiah upaya mengurangi kadar NaCl pada air laut yang berpotensi menjadi air layak minum secara sederhana, berbiaya murah dengan memanfaatkan limbah sekitar tempat tinggal (Batang Pisang, Enceng Gondok dan Abu Gosok). Penelitian ini merupakan penelitian eksperimen laboratorium. Untuk menentukan kadar NaCl sebelum dan sesudah dilewatkan adsorben dapat dilakukan menggunakan teknik analisa argentometri. Teknik analisa argentometri tergolong mud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Based on the calculation results, it was found that the ability of rice husk ash as an adsorbent in reducing phosphate levels in household wastewater was 52.54%. This result is smaller than when the rice husk ash was used as an adsorbent to reduce the NaCl content, which reached 83.75% [15].…”
Section: The Concentration Of Phosphate In the Sample Before And Afte...mentioning
confidence: 75%
See 1 more Smart Citation
“…Based on the calculation results, it was found that the ability of rice husk ash as an adsorbent in reducing phosphate levels in household wastewater was 52.54%. This result is smaller than when the rice husk ash was used as an adsorbent to reduce the NaCl content, which reached 83.75% [15].…”
Section: The Concentration Of Phosphate In the Sample Before And Afte...mentioning
confidence: 75%
“…Rice husk ash is one of the combustion wastes or ash from plants which usually comes from rice husks, the rest of the brick industry burning, and so on. Rice husk ash has a chemical composition of 53.09% SiO2, 24.80% Al2O3, and 8.01% Fe2O3 [15]. The ability of rice husk ash as an adsorbent has been widely studied, for example, reducing levels of congo red, removal of HCN in Gadung tubers, Cr +6 ions, adsorbent Cd ions and Cr ions, decreased industrial wastewater dyestuffs, Pb metal, decreased NaCl levels [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…With the reduced value of turbidity due to organic compounds, the BOD value will also decrease [10]. In addition, the faster the stirring will affect the reduced efficiency of BOD reduction which causes the BOD value to increase (Junaidi et al, 2020).…”
Section: Results Of Bod and Cod Analysismentioning
confidence: 99%
“…After settling in the form of floc, the amount of oxygen in the water will increase again. The decrease in the number of suspended particles in the liquid waste increases so that the COD value decreases (Junaidi et al, 2020).…”
Section: Efficiency Of Chitosan Snail Shells As Biocoagulants In Removal Of Cod (Chemical Oxygen Demand)mentioning
confidence: 99%
“…Dalam pengolahan data pada pengujian validitas penguji menggunaka tingkat signifikansi sebesar 10%, maka derajat kebebasan (df) = n-2, atau pada penelitian ini yaitu df = 100 -2 = 98. Maka nilai r tabel dapat dilihat pada tabel r yaitu df = 98 dengan r tabel = 0.1654 [20]. Seperti yang terlihat dari hasil perhitungan pada tabel 3, hasil yang diperoleh yaitu tidak adanya atribut yang perlu dibuang karena r hitung ≥ r tabel.…”
Section: Uji Validitas Dan Uji Relibilitas Dataunclassified